BIOCONTROL ABILITY OF Trichoderma harzianum ON GROWTH, DISEASE INCIDENCE AND YIELD OF SELECTED COWPEA VARIETIES (Vigna unguiculata L.) INFESTED WITH Colletotrichum lindemuthianum - ABDULKADIR A. I.,; HAYATU M.,; SANI, L. A.,; AHMED H., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Cowpea anthracnose caused by Colletotrichum lindemuthianum causes about 75 % yield reduction in Cowpea production in Nigeria. Trichoderma harzianum is a bioagent in controlling fungal diseases. Effect of T. harzianum was investigated on growth, disease incidence and yield of selected varieties of Cowpea infested with C. lindemuthianum. Four improved Cowpea varieties were selected IT07K-292-10, IT07K-318-33, IT98K-205-08, IT99K-573-11 and a local variety DANMISRA. Pure isolate of Colletotrichum lindemuthianum and Trichoderma harzianum were each cultured on PDA. Four concentrations of T. harzianum suspensions were prepared at 1x102 conidia/ml, 1x104 conidia/ml, 1x106 conidia/ml, 1x108 conidia/ml and control . Cowpea seedlings were artificially infested with 1x107conidia/ml of C. lindemuthianum at 22 days after sowing. The experiment was arranged in a complete randomized design (CRD) with three replications. The result indicated that the infested variety IT99K-573-11 treated with T. harzianum at 1x108 conidia/ml was insusceptible and had significantly (p<0.05) increased biomass, number of seeds and low disease incidence (19.1 %) while increase in chlorophyll content, seed number and decreased in the anthracnose incidence was observed at 1x108 conidia/ml concentration. The cultivar IT99K-573-11 appeared tolerant hence is recommended to farmer for cultivation in C. lindemuthianum infested areas.